2009
DOI: 10.1007/s11818-009-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Structuring the inter-individual variation in waking EEG can help to discriminate between the objective markers of sleep debt and sleep pressure

Abstract: Modern society is characterized by the steadily increasing demand and desire for wakefulness at all hours of the day. Research in the fields of sleep physiology and chronophysiology can offer instruments enabling the identification of people with and without advantageous traits, such as little need for sleep, decreased sleepiness associated with sleep loss, and rapid adaptation to changes in the workrest schedule. These instruments can also help to quantify the severity of sleep-wake disorders (i.e., excessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
(30 reference statements)
3
15
0
Order By: Relevance
“…Both our previous [17,19,20] and present findings on principal component structure of EEG spectra provide strong evidence for the generality of the loading patterns of the three largest principal components of spectrum variance (. Fig.…”
Section: Description Of Sleep and Wake States As A Function Of Princisupporting
confidence: 77%
See 2 more Smart Citations
“…Both our previous [17,19,20] and present findings on principal component structure of EEG spectra provide strong evidence for the generality of the loading patterns of the three largest principal components of spectrum variance (. Fig.…”
Section: Description Of Sleep and Wake States As A Function Of Princisupporting
confidence: 77%
“…In particular the studies employing EEG spectral analysis found that some patterns of EEG spectra might serve as markers of sleep pressure because they respond to the increase in sleepiness from sleep deprivation and other factors ( [7]). However, there is no agreement on gold standard indices for tracking changes in sleep pressure or for quantifying transitions from active waking to sleepiness ( [18,19,20] for more detail).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol of the experimental study has been extensively described in the previously published papers (Putilov et al 2009(Putilov et al , 2010. The experiments were conducted during early fall months (August andSeptember, 2006-2008) in accordance with the ethical standards laid down in the Declaration of Helsinki.…”
Section: Experimental Datamentioning
confidence: 99%
“…The results on objective (i.e. EEG) indexes of alertness-sleepiness were reported elsewhere (Putilov et al 2009(Putilov et al , 2010. Participants also completed several questionnaires at the time intervals between the measurements of EEG and performance.…”
Section: Methodsmentioning
confidence: 99%